Therapeutic targeting of non-coding RNAs in cancer - Slaby, Ondrej; Laga, Richard; Sedlacek, Ondrej (Biochemical journal, 2017)
The majority of the human genome encodes RNAs that do not code for proteins. These non-coding RNAs (ncRNAs) affect normal expression of the genes, including oncogenes and tumour suppressive genes, which make them a new class of targets for drug development in cancer. Although microRNAs (miRNAs) are the most studied regulatory ncRNAs to date, and miRNA-targeted therapeutics have already reached clinical development, including the mimics of the tumour suppressive miRNAs miR-34 and miR-16, which reached phase I clinical trials for the treatment of liver cancer and mesothelioma, the importance of long non-coding RNAs (lncRNAs) is increasingly being recognised. Here, we describe obstacles and advances in the development of ncRNA therapeutics and provide the comprehensive overview of the ncRNA chemistry and delivery technologies. Furthermore, we summarise recent knowledge on the biological functions of miRNAs and their involvement in carcinogenesis, and discuss the strategies of their therapeutic manipulation in cancer. We review also the emerging insights into the role of lncRNAs and their potential as targets for novel treatment paradigms. Finally, we provide the up-to-date summary of clinical trials involving miRNAs and future directions in the development of ncRNA therapeutics.